The influence of visual input and attention on gait initiation in people with Parkinson disease - Chelsea Parker Duppen; Jenevieve Surkin; Shefaali Mahendar; Jordan Saunders; Jenna Cole; Nina Browner; Michael D. Lewek (PLoS ONE, 2026)
Introduction Gait initiation relies on the integration of postural control, sensory input, and attention. All three components are impaired in Parkinson disease, which may contribute to characteristic gait initiation deficits, including shorter, slower first steps and smaller anticipatory postural adjustments. Understanding how sensory and attentional demands influence gait initiation could inform interventions that target underlying mechanisms rather than focusing solely on managing symptoms. This study examined the roles of vision and attention on gait initiation in people with Parkinson disease compared to older adult controls. We hypothesized that altering visual input and attentional demands would worsen gait initiation in both groups, with stronger effects in people with Parkinson disease. We also expected an interaction between visual input and attentional demands for people with Parkinson disease, further exacerbating impairment. Methods Sixteen people with Parkinson disease (Hoehn & Yahr stages I-III, on medication), and 16 older adults (aged 55+) initiated gait under four visual conditions: unaltered input, partial occlusion, full occlusion, and additional visual stimuli, each performed with and without a cognitive dual task. We measured first step length, first step speed, and anticipatory postural adjustment size to compare between groups and conditions. Results No interaction effects between group and condition were observed (all p ≥ 0.159). Full visual occlusion resulted in reduced first step length, first step speed, and anteroposterior anticipatory postural adjustment size (p ≤ 0.006). Partial occlusion resulted in decreased first step length and increased mediolateral anticipatory postural adjustment size (p ≤ 0.049). Gait initiation under a cognitive-motor dual task condition resulted in decrements across all variables (p ≤ 0.007). Conclusions Reduced visual input and increased attentional demands impair gait initiation in older adults and people with Parkinson disease. These findings highlight the roles of visual input and attention during gait initiation, but suggest visuo-attentional deficits may not uniquely contribute to hypokinesia in this population.